Analisis Faktor â€“ Faktor Yang Mempengaruhi Pendapatan Tenaga Kerja Industri Songkok Kota Gresik (Studi Pada Perusahaan Songkok â€œAwing dan Sonâ€ Kelurahan Pekelingan Kecamatan Gresik Kabupaten Gresik) - Rahmita, Nurina Widya (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2016)
This research aimed to analyze and identify the factors that affect labor income of skullcap industry in Gresik. The study was conducted at â€œAwing and Sonâ€ skullcap industry in Pekelingan, Gresik. The independent variables of this research are age (X1), education (X2) , length of working (X3) and the number of family (X4), while the dependent variable is labor income (Y). The population of this research amounted to 55 respondents, and there is no sample because the research is using the whole population as respondents. Data analysis methods that used in this research is multiple linear regression. The resultin this research indicate that the independent variables which are age (X1), education (X2), length of working (X3) and the number of family(X4) significantly influence income (Y) as the dependent variable. Â Keywords: Labor income (Y), Age (X1), Education (X2 ), Length of working (X3), The number of family (X4)